The Role of School Principals Through Religious Programs in Motivating Students' Religiosity Levels - Wanda Puspita Sari; Samsilayurni; Nurlena (Journal of Educational Management Research, 2026)
This study aims to examine the role of the principal in motivating students’ levels of religiosity through the implementation of religious programs. The research employs a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving principals, religious education teachers, and students. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the principal plays an active role as a leader, motivator, and supervisor in organizing and overseeing various religious programs, including joint prayers, congregational prayers, Qur’an recitation (tadarus), infaq activities, religious extracurricular programs, and memorization of Asmaul Husna. These programs contribute positively to enhancing students’ religiosity, as reflected in their stronger commitment to religious values, increased participation in religious activities, and positive changes in attitudes and behavior. The study implies that effective leadership by school principals is crucial in strengthening students’ religious character through well-managed and consistently implemented religious programs. Such leadership can serve as a strategic model for character education in schools, particularly in fostering students’ moral and spiritual development.